Low-density lipoprotein decorated silica nanoparticles co-delivering sorafenib and doxorubicin for effective treatment of hepatocellular carcinoma. (1st January 2018) - Ye, Junfeng; Zhang, Ruoyan; Chai, Wengang; Du, Xiaohong
Abstract: Combinational therapy is usually considered as a preferable approach for effective cancer therapy. Especially, combinational chemotherapies targeting different molecular targets are of particular interest due to its high flexibility as well as efficiency. In our study, the surface of silica nanoparticles (SLN) was modified with low-density lipoprotein (LDL) to construct platform (LDL-SLN) capable of specifically targeting low-density lipoprotein receptors (LDLRs) that overexpressing in hepatocellular carcinoma (HCC). In addition, the versatile drug loading capacity of LDL-SLN was employed to fabricate a preferable drug delivery system to co-deliver sorafenib (Sor) and doxorubicin (Dox) for combinational chemotherapy of HCC. Our results revealed that the LDL-SLN/Sor/Dox nanoparticles with size around 100 nm showed preferable stability in physiological environments. Moreover, the LDL-SLN/Sor/Dox could target LDLR overexpressed HepG2 cells. More importantly, both in vitro and in vivo experiments demonstrated that the LDL-SLN/Sor/Dox exerted elevated antitumor efficacy compared to Sor or Dox alone, which indicated that LDL-SLN/Sor/Dox could be a powerful tool for effective combinational chemotherapy of HCC.